PROSES KREATIF BATIK TULIS KONTEMPORER SEBAGAI MEDIA EKSPRESI MASA PANDEMI - Amaliana, Melitha; Nurcahyanty, Desy; Suherlan, Yayan (Visualita Jurnal Online Desain Komunikasi Visual, 2021)
Abstract, Batik activity includes techniques to decorate fabrics with certain motifs, as a medium of expression, education and contemplation for batik maker. The resulting products can be called works of art because batik maker dominate the concepts and ideas being visualized. Pembatasan Sosial Berskala Besar (PSBB) nationally during the pandemic caused psychological problems, namely saturation, because people were restricted from doing activities as a way to reduce the increase in the number of Covid-19 sufferers. The problem of boredom is also experienced by a batik maker from Girilayu, one of the women batik maker in Girilayu named Yuliasih, who has changed her perspective on making batik to eliminate boredom. Batik activity was originally positioned as a routine, by Yuliasih turned into a medium of expression during the pandemic. This study aims to determine Yuliasih's background in using batik as a medium of expression during the pandemic and the creative process that Yuliasih undertakes in her work. This research is qualitative descriptive with data collection methods using direct field observation to the location, namely Wahyu Asih's batik house, in-depth interviews with Yuliasih and community leaders in Girilayu and literature study. The analysis used triangulation in order to obtain data validity. The results of this study indicate that in addition to saturation, economic and cultural background is a consideration for Yuliasih to make batik as a medium of expression just like painting. Make batik is Yuliasih’s way to pour her expression and calming herself during pandemic